2015
DOI: 10.1002/mar.20813
|View full text |Cite
|
Sign up to set email alerts
|

Evaluative Conditioning of Food Technologies

Abstract: Consumer attitudes play an important role in the acceptance of new technologies. The success of food innovations depends on understanding how consumers form and change attitudes toward food technologies. Earlier post hoc explanations suggest that evaluative conditioning can change consumer attitudes toward food technologies. The present study tests how evaluative conditioning can affect consumer acceptance of new food technologies. Furthermore, authors investigate whether evaluative conditioning is resistant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Newly introduced food technologies might be perceived as risky due to their names, the media debate about them or because of the formation of a strong social opposition [52]. Genetic technology tends to evoke strong negative attitudes, while consumers appear to have positive attitudes towards conventional technologies [53]. However, GM foods are more likely to be accepted when their benefits are concrete, tangible and personally relevant [54].…”
Section: Discussionmentioning
confidence: 99%
“…Newly introduced food technologies might be perceived as risky due to their names, the media debate about them or because of the formation of a strong social opposition [52]. Genetic technology tends to evoke strong negative attitudes, while consumers appear to have positive attitudes towards conventional technologies [53]. However, GM foods are more likely to be accepted when their benefits are concrete, tangible and personally relevant [54].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have tested moderators in the lab that are relevant to marketing in the real world. For example, studies have found persistence of EC effects over time (e.g., Loebnitz & Grunert 2015), and generalization to other similar products (e.g., Till & Priluck 2000). Others found that the fit between the CS and the US matters (e.g., pairing a sports drink [CS] with Michael Jordan [US] leads to stronger effects than pairing it with Pierce Brosnan [US]; Till et al 2008).…”
Section: Ec In the Marketing Domainmentioning
confidence: 99%
“…In the presence of irrational behaviors, customers may contrast new food technologies, this is a phenomenon known as technophobia (Gorgitano, Verneau, and Sodano 2017). To obstruct technophobia and change consumer attitudes toward food technologies adoption, firms need to associate food innovations with positive pictures, which not only has immediate benefits but also prevents positive effects from extinction (Loebnitz and Grunert 2015). Briefly, to launch a successful new food product in the market, it is advocated to involve the customers in the food development process for improving consumers' acceptance (Busse and Siebert 2018).…”
Section: Digital Transformation In the Agri-food Industrymentioning
confidence: 99%